Coevolución y cocreación: una mirada ecológica de la inteligencia híbrida en la fase de preproducción de los medios audiovisuales (Monográfico) - Castro Hurtado, José Javier (2024)
This article examines the emerging relationship between humans and artificial intelligence (AI) in the preproduction phase of the audiovisual media industry. In this endeavor, adopting an interdisciplinary perspective grounded in media ecology theory and actor–network theory (ANT), two contrasting scenarios of this interaction are explored. On the one hand, mutualism, where humans and artificial species collaborate to improve the efficiency and quality of the creative process, is presented through the analysis of ScriptBook and Cinelytic, two of the most important used AI tools in the film industry. In addition, the dystopian threat is raised, where AI could replace human scriptwriters in the audiovisual media ecosystem, as illustrated by the strike of the Hollywood producers’ and screenwriters’ unions in 2023. These scenarios raise questions about the future of the industry and the coevolution between humans and AI through the concept of mutation. Emphasis is placed on the need to adapt to these transformations, recognizing the fundamental role of researchers and society in monitoring the relationship between humans and AI to understand its potential for co-creation and coevolution. Finally, the importance of agile adaptation to a constantly changing media ecosystem is underscored as an essential task to fully leverage the potential of hybrid intelligence and ensure the survival of the human species in this new technological paradigm.